2005
DOI: 10.1080/08880010590907267
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine in Chronic Granulomatous Disease

Abstract: Chronic granulomatous disease (CGD) is a rare genetically determined immunodeficiency. Neutrophils from CGD patients show a defective killing of phagocytosed fungi and bacteria, due not only to an impairment in oxidative burst, but also to absence of normal pH value within phagocytic vacuole following phagocytosis. Because a weak base such as amantadine could potentially reverse these pH abnormalities, the authors used this drug to treat 2 CGD patients. They observed modifications of both phagosomal pH and kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In agreement with our findings, the NADPH oxidase complex that produces superoxide is effective only at near-neutral pH, because a more neutral environment has been found to be more conducive to oxidation-mediated killing of pathogens (36). Interestingly, phagocytes isolated from chronic granulomatous disease (CGD) model mice, a primary immunodeficiency in which a genetic defect in the NADPH oxidase results in diminished reactive oxygen species production, have been shown to contain more acidic phagosomes than seen in normal WT cells and are thus unable to kill ingested pathogens (3739) despite the presence of normal to high concentrations of NO (40, 41). Given our findings, it is not surprising that patients with CGD are particularly susceptible to infection by heavily encapsulated microbes (42, 43), including Staphylococcus aureus that carry T cell activating GlyAgs in their capsule (44) and Aspergillus species.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, the NADPH oxidase complex that produces superoxide is effective only at near-neutral pH, because a more neutral environment has been found to be more conducive to oxidation-mediated killing of pathogens (36). Interestingly, phagocytes isolated from chronic granulomatous disease (CGD) model mice, a primary immunodeficiency in which a genetic defect in the NADPH oxidase results in diminished reactive oxygen species production, have been shown to contain more acidic phagosomes than seen in normal WT cells and are thus unable to kill ingested pathogens (3739) despite the presence of normal to high concentrations of NO (40, 41). Given our findings, it is not surprising that patients with CGD are particularly susceptible to infection by heavily encapsulated microbes (42, 43), including Staphylococcus aureus that carry T cell activating GlyAgs in their capsule (44) and Aspergillus species.…”
Section: Discussionmentioning
confidence: 99%
“…Note that defective phagocytosis is involved in the development of a large number of disorders like chronic granulomatous disease. [27] Previously, we have shown that compound 2 internalizes easily into living RAW 264.7 mouse macrophages and accumulates in the lysosomes, as characterized by an acidic pH. [32] This was demonstrated by confocal laser scanning www.eurjoc.orgmicroscopy (CLSM) using for comparison two commercial lysosome markers such as DND-189 and DND-26.…”
Section: Phagocytosis Assaysmentioning
confidence: 97%
“…The pH reported for these acidic vesicles varies within the range 4.0-6.5 depending on the biochemical processes taking place and, in comparison with the vast collection of available pH sensors for the neutral regions, [20,24,26] the number of useful acidic probes is much reduced. [21,23] The synthesis of new families of fluorescent probes for acidic intracellular environments is important not only for basic biochemical research but also for the potential applicability of such probes as diagnostic tools for disorders associated with unbalanced acidity at the cellular level, such as chromic granulomatous disease, [27] mucolipidosis type IV, [28] Batten disease, [29] and several oncological processes. [30] In fact, the unbalanced acidity of cancerous tissues was first recognized by Warburg decades ago [31] and such knowledge has led to new approaches for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 × 10 –8 mol L –1 . Slight variation in this value can impair enzyme activities, 2 synaptic transmission, 3 and appears to play a role in Alzheimer's, 4 chronic granulomatous disease, 5 mucolipidosis type IV, 6 as well as cardiopulmonary and neurological conditions. 7 Furthermore, abnormal alteration in cytosolic and vesicular acidity has been associated with cancer.…”
Section: Introductionmentioning
confidence: 99%